2006
DOI: 10.1073/pnas.0603704103
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism of microtubule stabilization by Taxol

Abstract: The antitumor drug Taxol stabilizes microtubules and reduces their dynamicity, promoting mitotic arrest and cell death. Upon assembly of the ␣͞␤-tubulin heterodimer, GTP bound to ␤-tubulin is hydrolyzed to GDP reaching a steady-state equilibrium between free tubulin dimers and microtubules. The binding of Taxol to ␤-tubulin in the polymer results in cold-stable microtubules at the expense of tubulin dimers, even in the absence of exogenous GTP. However, there is little biochemical insight into the mechanism(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
250
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(271 citation statements)
references
References 41 publications
12
250
2
1
Order By: Relevance
“…In addition, our 2ME2-resistant leukemia cells acquired two novel mutations in class I h-tubulin, S25N and A248T, which were confirmed at the protein level by MS analysis. The S25N mutation is at the NH 2 terminus of h-tubulin (28) and forms part of the paclitaxel-binding pocket (29). Furthermore, this mutation is close to the htubulin M-loop, which forms major lateral interactions in microtubule assembly (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our 2ME2-resistant leukemia cells acquired two novel mutations in class I h-tubulin, S25N and A248T, which were confirmed at the protein level by MS analysis. The S25N mutation is at the NH 2 terminus of h-tubulin (28) and forms part of the paclitaxel-binding pocket (29). Furthermore, this mutation is close to the htubulin M-loop, which forms major lateral interactions in microtubule assembly (30).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments found that, in vivo, such a delicate balance is maintained because of a variety of factors that modulate the dynamic instability of MTs: GTP hydrolysis (3,9), molecular motors such as Kin-13 and other microtubuleassociated proteins (MAPs), and cofactors such as E and B, which increase the depolymerization rate (10,11); MAPs such as CLIP-170, which stabilize the MT lattice preventing catastrophes (12); and katanin and spastin, which sever MTs (13). However, in vitro MT dynamic instability occurs under modest conditions: either as a result of GTP hydrolysis (14) or under cold denaturation even in a nonhydrolyzable GMPCPP MT variant (9).…”
mentioning
confidence: 99%
“…Because of their dynamic instability, i.e., stochastic alternation of slow growth and rapid shrinking phases between MTs and soluble tubulin subunits, MTs are able to transport chromosomes and other cellular organelles inside the cell (1). Blockage of dynamic instability by drugs such as taxol, which reduce the flexibility of the MT structure, promotes mitotic arrest and leads to cell death (2,3). This behavior makes MTs a main target for cancer drugs (2), but efforts to design effective drugs are hampered, in part, by the lack of clear understanding of the microscopic origin of MT instability and of the MT behavior under tension (4).…”
mentioning
confidence: 99%
“…Deuterium incorporation of the microtubules was then measured, providing a picture of the conformational changes between free tubulin and Taxolbound tubulin. Taxol was found to modify tubulin conformation not just at the binding sites but at allosteric sites as well (1). The results indicated that, whereas in the absence of Taxol the tubulin dimers can adopt a curved conformation associated with the destabilization of microtubules, in the drug's presence the dimer is locked into a straight conformation promoting assembly of microtubules and stabilization.…”
Section: ''I Loved the Idea That Small Molecules Could Do Great Thingmentioning
confidence: 80%